The Impact of Sustainable Financing, Dividend Policy, and Capital Structure on Firm Value: An Empirical Study of Banks Listed on the Indonesia Stock Exchange - Rusdi, Elman Junizar; Risman, Asep (Universitas Mercu Buana, 2025)
This study aims to analyze the impact of sustainable financing, dividend policy, and capital structure on firm value, with a particular focus on the banking subsector listed on the Indonesia Stock Exchange (IDX). A quantitative analysis approach is employed to ascertain the relationship between the independent variables namely, the sustainable financing ratio, the dividend payout ratio (DPR), and the debt to equity ratio (DER) and the dependent variable, firm value, which is measured by the price to earnings ratio (PER). The study employs panel data regression analysis using the R-4.4.2 software packages. The sample comprises seven banking companies, selected using purposive sampling, with a total of 21 observations derived from annual financial statements and sustainability reports covering the period 2021-2023. The findings demonstrate that sustainable financing exerts a substantial negative influence on firm value, indicating that an augmentation in sustainable financing can actually diminish the market value of the company. Similarly, dividend policy has also been found to have a negative effect on firm value, while capital structure has been observed to have a positive but statistically insignificant effect. It is anticipated that this study will provide insights for management and investors, emphasizing the importance of balancing these financial variables in decision-making in order to enhance company performance and investment strategies.